2005
DOI: 10.1111/j.1365-2583.2004.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of alternative splicing in the silkworm by aligning expressed sequence tags with the genomic sequence

Abstract: We identified 277 alternative splice forms in silkworm genes based on aligning expressed sequence tags with genomic sequences, using a transcript assembly program. A large fraction (74%) of these alternative splices are located in protein-coding regions and alter protein products, whereas only 26% are in untranslated regions. From the alternative splices located in protein-coding regions, some (43%) affect protein domains that bind various biological molecules. The vast majority of the detected alternative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The sequence analysis showed that Ld-GRP2v2 mRNA had two poly(A) adding sites leading to the formation of Ld-GRP2 and Ld-GRP2v2. The length of 3 ′ UTR is positively related to the stability of mRNA and thus to the amount of the gene product (Stamm et al ., 2005;Zha et al ., 2005). Such a positive correlation is found between the lengths of 3 ′ UTR of mKIAA cDNA and the relative expression in adult mouse brains (Okazaki et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The sequence analysis showed that Ld-GRP2v2 mRNA had two poly(A) adding sites leading to the formation of Ld-GRP2 and Ld-GRP2v2. The length of 3 ′ UTR is positively related to the stability of mRNA and thus to the amount of the gene product (Stamm et al ., 2005;Zha et al ., 2005). Such a positive correlation is found between the lengths of 3 ′ UTR of mKIAA cDNA and the relative expression in adult mouse brains (Okazaki et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, these are insufficient to provide a global view of alternative splicing and trans-splicing in the silkworm. Only 277 alternative splicing events were identified in a previous study based on the available EST sequences (Zha et al 2005). Recently, powerful high-throughput sequencing technology (RNA-seq) has been widely applied to transcriptome profiling and has been shown to be an effective and accurate method for the identification of novel transcripts and alternative splicing and trans-splicing events in many organisms, including D. melanogaster, C. elegans, rice, and human Zhang et al 2010;Daines et al 2011;Graveley et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of introns in the 5′-UTR regions are diverse. A recent study has established that alternative splicing is a common phenomenon in the silkworm, and that the alternative translation initiation that occurs as a consequence of alternative splicing accounts for 25% of all the observed protein alterations (Zha et al, 2005). For this reason, alternative IRES have been sought in the three 5′-UTR gene sequences, albeit without success.…”
Section: Discussionmentioning
confidence: 98%